Analytical Rigor in Studies of Disparities in Criminal Case Processing - Wooldredge, John D. (Journal of quantitative criminology, 1998)
Studies of racial/ethnic disparities in criminal case processing have yielded mixed results. Some differences in findings have probably resulted from analyses of different social settings, but some could be attributable to differences in analytical rigor between studies. Contextual analyses are pointless unless the research yields unbiased estimates of the true relationships between a defendant's race/ethnicity and case dispositions. This goal may be furthered by conducting analyses that simultaneously incorporate the following: (a) corrections for sample bias, (b) analyses of several stages of case processing, (c) measures of prior record and offense seriousness which maximize “explained” variation in the dependent variables examined, (d) statistical controls for extralegal variables that correlate with case dispositions, and (e) more rigorous statistical tests for interactions. To demonstrate potential differences in findings from analyses with and without these characteristics, results from a study of 1586 Mexican- and Anglo-American defendants from Dona Ana County, New Mexico, are presented.